Prevalence of Obstructive Sleep Apnea in Patients With Diabetic Foot Ulcers - Chen, Lihong; Ma, Wanxia; Tang, Weiwei; Zha, Panpan; Wang, Chun; Chen, Dawei; Lei, Fei; Li, Taomei; Tang, Xiangdong; Ran, Xingwu (Frontiers in Endocrinology, 2020)
Objectives: Diabetic foot ulcers (DFUs) are a considerable burden on patients and the healthcare service system. Patients with DFUs have many risk factors which might contribute to obstructive sleep apnea (OSA). The purposes of this study were to assess the prevalence of OSA and associated features in patients with DFUs. Methods: Between July 2017 and June 2019, we recruited 245 consecutive patients who sought for treatment at West China Hospital because of diabetic foot ulcers. Polysomnography data from 127 Patients were included in the final analysis. Results: Of the 127 patients, with a median age of 64 years old (IQR 55-73, range 36-86), a mean BMI 24.09±0.37 Kg/m2, 91 (72%) were men. The prevalence of OSA (Apnea-hypopnea index, AHI >5/h) was 92% in men and 97% in women (P = 0.304). Moderate-to-severe OSA (AHI >15/h) was noted in 44 men (48%) and 26 women (72%) (P = 0.015). The risk factors associated with the severity of OSA were sex, age, smoking, alcohol use, duration of diabetes. After multivariable adjustment, duration of diabetes and age were independent predictive factor of the severity of OSA. No significant association was observed between BMI, waist circumstance, Epworth score and the severity of OSA. There were no significant associations between OSA and ischemic heart disease, cerebral infarction, hypertension, diabetic retinopathy, diabetic kidney disease, and peripheral artery disease. Conclusions: The prevalence of obstructive sleep apnea was high in patients with DFUs. Age and duration of diabetes were independent predictive factors of the severity of OSA.